The NICE-GUT trial protocol: a randomised, placebo controlled trial of oral nitazoxanide for the empiric treatment of acute gastroenteritis among Australian Aboriginal children. Issue 2 (1st February 2018) - Waddington, Claire S; McLeod, Charlie; Morris, Peter; Bowen, Asha; Naunton, Mark; Carapetis, Jonathan; Grimwood, Keith; Robins-Browne, Roy; Kirkwood, Carl D; Baird, Robert; Green, David; Andrews, Ross; et al.
Abstract : Introduction: Diarrhoeal disease is the second leading cause of death in children under 5 years globally, killing 525 000 annually. Australian Aboriginal and Torres Strait Islander (hereafter Aboriginal) children suffer a high burden of disease. Randomised trials in other populations suggest nitazoxanide accelerates recovery for children with Giardia, amoebiasis, Cryptosporidium, Rotavirus and Norovirus gastroenteritis, as well as in cases where no enteropathogens are found. Methods and analysis: This double blind, 1:1 randomised, placebo controlled trial is investigating the impact of oral nitazoxanide on acute gastroenteritis in hospitalised Australian Aboriginal children aged 3 months to <5 years. Dosing is based on age-based dosing. The primary endpoint is the time to resolution of 'significant illness' defined as the time from randomisation to the time of clinical assessment as medically ready for discharge, or to the time of actual discharge from hospital, whichever occurs first. Secondary endpoints include duration of hospitalisation, symptom severity during the period of significant illness and following treatment, duration of rehydration and drug safety. Patients will be followed for medically significant events for 60 days. Analysis is based on Bayesian inference. Subgroup analysis will occur by pathogen type (bacteria, virus or parasite), rotavirus vaccination status, age and illness severity. Ethics and dissemination: Ethics approval has been granted by the Central Australian Human Research Ethics Committee (HREC-14–221) and the Human Research Ethics Committee of the Northern Territory Department of Health and Menzies School of Health Research (HREC2014-2172). Study investigators will ensure that the trial is conducted in accordance with the principles of the Declaration of Helsinki. Individual participant consent will be obtained. Results will be disseminated via peer-reviewed publication. Trial registration number: ACTRN12614000381684 .